A Beam-Angle-Selection Method to Improve Inter-Fraction Motion Robustness for Lung Tumor Irradiation With Passive Proton Scattering. (25th August 2020) - Zhang, Yawei; Ho, Meng Wei; Li, Zuofeng
In terms of dose distribution, protons are more sensitive to range variations than photons due to their unique properties. The aim of this study was to develop a method to identify patient-specific robust proton beam angles for lung tumor irradiation by investigating the association between water equivalent thickness (WET) variation and inter-fraction motion-induced target dose degradation. Using 3-dimensional computed tomography (3D-CT) images, the impact of WET variations on the target dose coverage of a series of coplanar proton beams was evaluated for 4 patients with lung cancer. Using ray tracing, WET maps, or WET baseline, were estimated for the internal target volume (ITV) at every 5° gantry interval in the axial plane. After calculating the WET baseline, the planning CT was shifted 5 mm in each anterior-posterior (AP), superior-inferior (SI), and left-right (LR) direction, yielding a total of 6 shifted CTs, and differential WET maps between the planning CT and each shifted CT were calculated. Target dose differences were associated with the average WET change between the original planning CT and the shifted CTs for all 360° gantry rotation beams. Target and OAR dose metrics in the ΔWET-guided plans were compared with those of the clinical plans. The WET variation maps showed areas of both high and low WET variations, with overall similar patterns yet individual differences reflecting tumor position differences. For all 4 patients investigated in this study, the coplanar plans demonstrated a strong correlation between WET changes and ITV dose reductions. Target dose coverage was more stable with the ΔWET-guided plan while OAR doses were comparable to the clinical plan. The WET variation maps have been used in this pilot study to identify proton beam angles that are either sensitive or robust to WET changes in proton passive scattering. This work demonstrates the feasibility of using WET variation maps to assist the planner in inter-fraction motion-robust proton beam angle selection.